Effects of post-activation enhancement (PAPE) in elite volleyball players - Masel, S.; Maciejczyk, M. (27th Annual Congress of the European College of Sport Science (ECSS), Sevilla, 30. Aug - 2. Sep 2022, 2022)
INTRODUCTION: Post-activation performance enhancement (PAPE) is a widely described physiological phenomenon showing increases in exercise performance after previous muscle activation (1). Throughout the years authors have been studying the phenomenon but so far there was not found a consensus what are the ideal parameters of a conditioning activity (CA) to induce PAPE (2). However, authors generally tend to focus on different parameters of a CA and its responses on a given test. Our approach was different - we decided to evaluate the responses of the same CA in two different jumping tests: countermovement jump (CMJ) and squat jump (SJ). Additionally, accommodating resistance via elastic band was used to induce PAPE - a training method that is widely used in the sport and was already used in PAPE research (3).